Liver Cancer Survival: A Real World Observation of 45 Years with 32,556 Cases - Chen JG; Zhu J; Zhang YH; Chen YS; Ding LL; Chen HZ; Shen AG; Wang GR (Journal of Hepatocellular Carcinoma, 2021)
Jian-Guo Chen,1,2 Jian Zhu,1 Yong-Hui Zhang,1 Yong-Sheng Chen,1 Lu-Lu Ding,1 Hai-Zhen Chen,2 Ai-Guo Shen,2 Gao-Ren Wang2 1Department of Epidemiology, Qidong Liver Cancer Institute, Qidong People’s Hospital, Affiliated Qidong Hospital of Nantong University, Qidong, People’s Republic of China; 2Cancer Institute, Nantong Tumor Hospital, Affiliated Tumor Hospital of Nantong University, Nantong, People’s Republic of ChinaCorrespondence: Jian-Guo Chen Qidong Liver Cancer Institute, Qidong People’s Hospital, Affiliated Qidong Hospital of Nantong University; Cancer Institute, Affiliated Tumor Hospital of Nantong University, Nantong, People’s Republic of China Email chenjg@ntu.edu.cnBackground and Aims: To explore the long-term trend of liver cancer survival, based on the real-world data (RWD) in the past 45 years from a population-based cancer registry, in Qidong, China.Methods: A number of 32,556 patients with liver cancer were registered during the period of 1972 to 2016. Mixed methods by active and passive follow-up were performed. Life table method was employed for survival analysis by SPSS22 software. Wilcoxon (Gehan) statistics was considered as a significant test. Relative survival was calculated by using SURV software, and its annual percent change (APC) was estimated by the Joinpoint Regression Program.Results: The overall observed survival (OS) rates of 1-, 5-, 10-, and 20-year rates from the data series were 18.51%, 6.28%, 4.03%, and 2.84%, and their relative survival (RS) rates were 18.88%, 6.95%, 4.96%, and 4.49%, respectively. For 24,338 male cases, the 5-year OS and RS rates were 5.93% and 6.54%, and for 8218 female cases, 7.34% and 8.15%, respectively, with P values less than 0.01. Survival rates of liver cancer from three 15-year periods of 1972– 1986, 1987– 2001, and 2002– 2016 have increased significantly, with 5-year OS rates of 2.02%, 4.40%, and 10.76%, 5-year RS rates of 2.18%, 4.83%, and 12.18%; 10-year OS and RS rates of 0.95%, 3.00%, and 7.02%, vs 1.13%, 3.65%, and 8.96%, respectively, showing a very significant upward trend (P< 0.01). There are significant differences among age groups (P< 0.01): those aged 55– 64 demonstrated the best OS and RS rates of 5-year, being 8.44% and 9.09%, respectively.Conclusion: There are significant gender and age differences in the survival rate of liver cancer in Qidong. RWD indicates the relative lower survival rate of liver cancer in this area, but great improvement has been achieved over the past decades.Keywords: liver cancer, survival rate, long-term trend, real-world data, Qidong